Global reform population health management as stewarded by Higher Expert Medical Science Safety (HEMSS) - Henry, James Andrew (Frontiers in Artificial Intelligence, 2025)
As described in a Memorandum of Understanding (MoU) on AI infrastructure, global human phenotype ontology (HPO) is a priority for the US and the UK. The UK NHS Act of 1946 and the Medicare and Medicaid Act of 1965 classify using genomics as primary care, supporting international HPO aims for Population Health Management (PHM). The Higher Expert Medical Science Safety (HEMSS) proposes the NHS England, Genomics, and Biobank agile group developers. The HEMSS strategy executes the PHM of the HPO through digital records, pilot citizen predictor pre-eXams, and precise eXam intercept classifications, continuously improving public safety. PHM reform includes biobank opportunities for Value-Based Care (VBC) stratifying genomic and socio-environmental factors that risk HPO in disease segmentation. The author evaluated a standard approach to PHM for HPO with mature and advanced interoperable standards. A reform toolkit aligns adversarial, neural, and transformer models for Generative AI by utilizing multimodal data nuanced for fairness in Quantum Intelligence. The recommendations include HEMSS steps from well-being evaluations to the PHM strategy for HPO in the UK-US. Concepts involve piloting the scaling up of neighborhood clinics and federal centers through reform classification. Plans for citizen privacy facilitate data use with access to reference biobanks, ensuring DNA democratization and national cybersecurity. The UK NHSE corporate governance and US federal authorities monitor and reform the Integrated Care Board assessments and the Centers for Medicare and Medicaid Services surveys using agile methods. The UK-US MoU for AI safety is an international ideal for PHM, creating a safe space for HPO adherence to predictive and interceptive adoption for health and socioeconomic growth. HEMSS Agile Group Development impacts ethical and societal primary care debates. HEMSS discussions on global public health inclusiveness and national engagement aim to govern the classification phases for adherence. Therefore, debates on UK-US accreditation or regulation on the future of Artificial General Intelligence follow. The author concludes in support of the Population Health Management Expert Medical Science Safety Agile Group Development Program. The UK and US governments would benefit from this proposition, and international goals for well-being and socioeconomic growth would also be supported.